Varied Practice in Laparoscopy Training: Beneficial Learning Stimulation or Cognitive Overload? - Spruit, Edward N.; Kleijweg, Luca; Band, Guido P. H.; Hamming, Jaap F. (Frontiers in Psychology, 2016)
Determining the optimal design for surgical skills training is an ongoing research endeavor. In education literature, varied practice is listed as a positive intervention to improve acquisition of knowledge and motor skills. In the current study we tested the effectiveness of a varied practice intervention during laparoscopy training. Twenty-four trainees (control group) without prior experience received a 3 weeks laparoscopic skills training utilizing four basic and one advanced training task. Twenty-eight trainees (experimental group) received the same training with a random training task schedule, more frequent task switching and inverted viewing conditions on the four basic training tasks, but not the advanced task. Results showed inferior performance of the experimental group on the four basic laparoscopy tasks during training, at the end of training and at a 2 months retention session. We assume the inverted viewing conditions have led to the deterioration of learning in the experimental group because no significant differences were found between groups on the only task that had not been practiced under inverted viewing conditions; the advanced laparoscopic task. Potential moderating effects of inter-task similarity, task complexity, and trainee characteristics are discussed.